Respecting What We Destroy: Reflections on Human Embryo Research - Meyer, Michael J. (The Hastings Center report, 2001)
The thought that human embryos could command moral respect yet also be acceptably used in medical research has struck some as incoherent. Given some assumptions about why they deserve respect, however, the thought is not objectionable, indeed not even unusual.